Low Receipt and Uptake of Safer Conception Messages in Routine HIV Care: Findings From a Prospective Cohort of Women Living With HIV in South Africa. (1st May 2016) - Steiner, Riley J.; Black, Vivian; Rees, Helen; Schwartz, Sheree R.
Abstract : Background: Safer conception strategies may be used by people living with HIV to reduce HIV transmission to partners resulting from condomless sex for conception. The extent to which people living with HIV receive safer conception messages and use risk reduction strategies is largely unknown. Methods: We use prospective data from a clinic-based cohort study in Johannesburg, South Africa. Women living with HIV (WLWH) aged 18–35 on antiretroviral therapy (n = 831) completed a baseline survey and ≥1 follow-up visits assessing fertility intentions and pregnancy incidence; an endline survey was administered 1 year postenrollment. Multivariate negative binomial regression models examined differences in the number of condomless sex acts by fertility intentions. Chi-squared statistics compared receipt of safer conception messages by fertility intentions and indicators of safer conception method use by partner HIV status. Results: The median baseline age of participants was 30.4 years and 25.3% were in serodiscordant partnerships. WLWH trying to conceive were over 3 times more likely to have condomless sex compared with those not trying to conceive (adjusted incidence rate ratio: 3.17, 95% confidence interval: 1.95 to 5.16). Receipt of specific safer conception messages was low, although women with positive fertility intentions were more likely to have received any fertility-related advice compared with those with unplanned pregnancies (76.3% vs. 49.1%, P < 0.001). Among WLWH trying to conceive (n = 111), use of timed unprotected intercourse was infrequent (17.1%) and lower in serodiscordant vs. concordant partnerships (8.5% vs. 26.9%, P = 0.010). Conclusions: These findings suggest that clinic and patient-level interventions are needed to ensure that WLWH receive and use safer conception strategies.